2022
DOI: 10.3390/polym14214778
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrazine as an Extract from Medicinal and Edible Plant Chuanxiong Encapsulated in Liposome–Hydrogel Exerting Antioxidant Effect on Preventing Skin Photoaging

Abstract: Long-term sunlight exposure will cause the accumulation of free radicals in the skin and lead to oxidative damage and aging, antioxidant drugs have gradually become the focus of research, but there is little research on antioxidant drugs for percutaneous treatment. The purpose of this study was to prepare ligustrazine hydrochloride (TMPZ)-loaded liposome–hydrogel (TMPZ-LG), evaluate its antioxidant properties, and apply it on the skin of mice to observe whether it had preventive and therapeutic effect on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Under acidic and high temperature conditions, MDA can be condensed with thiobarbituric acid (TBA) to produce brown–red trimethylecylate, which can be detected at 532 nm. Studies have shown that the detection of MDA levels could be used as a test index for the symptoms of photoaged skin caused by ultraviolet exposure [ 58 ]. Fardin [ 59 ] used MDA as an antioxidant parameter to study oxidative stress degree in atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under acidic and high temperature conditions, MDA can be condensed with thiobarbituric acid (TBA) to produce brown–red trimethylecylate, which can be detected at 532 nm. Studies have shown that the detection of MDA levels could be used as a test index for the symptoms of photoaged skin caused by ultraviolet exposure [ 58 ]. Fardin [ 59 ] used MDA as an antioxidant parameter to study oxidative stress degree in atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…PAE-L was prepared using the thin-film dispersion method. Firstly, according to the ratio of phospholipid and cholesterol prescribed in our laboratory [ 58 ], 0.3 g phospholipid, 0.1 g cholesterol, and 0.0028 g paeonol were accurately weighed and placed into a 250 mL beaker, and then 5 mL anhydrous ethanol was added and placed into the ultrasonic cleaner (HS3120, Tianjin Hengao Technology Development Co., Ltd., Tianjin, China) to dissolve completely and quickly spread on the beaker wall rotary evaporator to form liposome film, and an appropriate amount of PBS was added to shake it with magnetic stirrers.…”
Section: Methodsmentioning
confidence: 99%
“…Female mice were dissected [ 9 ], and the livers were quickly removed, rinsed repeatedly with 4 °C saline, blotted dry on filter paper, weighed, rinsed with 9-fold cold saline, and homogenized with a glass homogenizer. After centrifugation for 15 min at 4000 rpm, 10% of the liver homogenate was prepared by taking the supernatant and was stored in a refrigerator at 4 °C (The selected quercetin concentrations were 1.15, 1.53, 2.3, 4.6, and 9.2 mg/mL, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Complications such as erythema, blisters, and epidermal detachment usually occur [ 6 , 7 ]. In human skin, about 2% of oxygen consumption is converted to ROS (reactive oxygen species); the accumulation of ROS leads to an inflammatory response and accelerated skin oxidation [ 7 , 8 , 9 ]. Therefore, it is important to find ways to protect against skin damage caused by ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Astragali Radix (Huangqi) 23 and Chuanxiong Rhizoma (Chuanxiong) 24 are medicinal and food homologous plants in traditional Chinese medicine, which rhizomes are the main edible medicinal parts. Consuming the rhizome with food is a typical therapy to keep healthy.…”
Section: Introductionmentioning
confidence: 99%